2002
DOI: 10.1038/sj.onc.1205339
|View full text |Cite
|
Sign up to set email alerts
|

Positional cloning identifies a novel cyclophilin as a candidate amplified oncogene in 1q21

Abstract: Gains of 1q21-q23 have been associated with metastasis and chemotherapy response, particularly in bladder cancer, hepatocellular carcinomas and sarcomas. By positional cloning of ampli®ed genes by yeast arti®cial chromosome-mediated cDNA capture using magnetic beads, we have identi®ed three candidate genes (COAS1, -2 and -3) in the ampli®ed region in sarcomas. COAS1 and -2 showed higher ampli®cation levels than COAS3. Most notably, ampli®cation was very common in osteosarcomas, where in particular COAS2 was hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 48 publications
1
35
0
1
Order By: Relevance
“…GOLPH3L is located at 1q21.3. It has been reported that 1q21 is amplified in several human malignancies, including rhabdomyosarcoma (16)(17)(18)(19)(20)(21)(22)(23)(24). An amplification of 5p13 has not yet been reported in rhabdomyosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…GOLPH3L is located at 1q21.3. It has been reported that 1q21 is amplified in several human malignancies, including rhabdomyosarcoma (16)(17)(18)(19)(20)(21)(22)(23)(24). An amplification of 5p13 has not yet been reported in rhabdomyosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…A novel cyclophilin, which is similar to CypA, has been associated with metastasis and is overexpressed in bladder cancer, hepatocellular carcinoma, sarcoma, and breast carcinoma. 10 However, there are no reports of CypA correlation with pancreatic cancer.…”
mentioning
confidence: 99%
“…Reflecting these biological potentials, the role of CypA has been studied in many types of malignant tumors, such as non-small cell lung carcinoma, pancreatic cancer, bladder cancer, hepatocellular carcinoma, sarcoma and breast cancer (20)(21)(22). These studies showed that CypA expression is up-regulated in tumor tissues and that CypA induces cancer cell proliferation and MMP expression, resulting in a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the homophilic binding of EMMPRIN, recent studies reported that cyclophilin A (CypA) acts as a ligand for EMMPRIN (17,18). The importance of the CypA-EMMPRIN interaction has been reported in rheumatoid arthritis (19), foam cell formation (17) and also in several solid tumors (20)(21)(22). However, the role of CypA and its interaction with EMMPRIN in HNSCC has not yet been evaluated.…”
Section: Introductionmentioning
confidence: 99%